The tumor distance to the main hepatic vessels is a predictor of recurrence-free survival and overall survival in hepatocellular cancer - Abdelhadi, Schaima; Rink, Johann; Froelich, Matthias F.; Şandra-Petrescu, Flavius Ionuţ; El-Ahmar, Mohamad; Oweira, Hani; Rahbari, Nuh Nabi; Reißfelder, Christoph; Birgin, Emrullah (Langenbeck's archives of surgery, 2025)
Introduction The impact of the distance of the tumor from the main hepatic vessels (DTV), such as the Glissonean pedicle or hepatic veins, on oncological outcomes for Hepatocellular carcinoma (HCC) patients is relatively understudied. Therefore, the objective of this study was to explore the correlation between DTV and survival in patients with HCC after curative hepatic resection. Methods Consecutive patients who underwent curative-intent liver surgery for HCC between April 2018 and May 2023 were identified from a prospective database. Univariate and multivariate Cox regression analysis were performed to identify independent predictors of recurrence-free survival (RFS). A ROC-curve was used to find the optimal cut-off value for DTV. According to the estimated cut-off value, patients were divided into 2 subgroups, then using the Kaplan-Meier survival curve, RFS and overall survival (OS) were estimated and compared between the 2 subgroups. Results In univariate analysis, DTV, tumor size, resection margins, microvascular invasion (MVI) and tumor grading were associated with RFS. In multivariate analysis, DTV, tumor size, and MVI were confirmed as independent predictors of RFS. In the ROC-analysis the optimal cutoff value of DTV was 20 mm. Patients with a DTV < 20 mm had a larger tumor size and a more advanced histopathological grading. There was no difference in the presence of MVI in both groups, while a significantly more patients experienced recurrence after hepatectomy in the DTV < 20 mm group. Accordingly, patients with a DTV < 20 mm experienced a shorter median RFS and OS. Conclusion DTV is a promising predictor of RFS and OS in HCC.
Online veröffentlicht: 9. Januar 2025
Gesehen am 24.07.2025